Mental health burden among females living with HIV and AIDS in sub-Saharan Africa: A systematic review - Boakye, D.S.; Setordzi, M.; Dzansi, G. (Plos Global Public Health, 2024)
Mental health problems, particularly depression and anxiety, are common in women and young girls living with HIV/ AIDS particularly in low- and middle-income (LMICs) countries where women’s vulnerability to psychiatric symptoms is heightened due to the prevalent intersectional stressors such as stigma and intimate partner violence. However, no synthesized evidence exists on the mental health burden of females living with HIV/AIDS (FLWHA) in Africa. This systematic review aimed to synthesize the current evidence on the mental health burden among FLWHA in sub-Saharan Africa. A systematic literature review of articles published from 2013–2023 was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines (PRISMA). Five electronic databases; PubMed, MEDLINE with full text, Scopus, Academic Search Complete, and Health Source: Nursing Academic Edition were searched for articles published in English. Nineteen articles (15 quantitative, 3 qualitative, and 1 case study) from over 7 African countries met the inclusion criteria. The majority of the studies’ quality was determined to be moderate. The prevalence of depression ranged from 5.9 to 61% and anxiety from 28.9 to 61%. Mental health burden was a logical outcome of HIV diagnosis. Predic tors of mental health outcomes in the context of HIV/AIDS were identified as intimate partner violence (IPV), stigma, childhood traumas, sexual abuse, poverty, unemployment, and social isolation. Social support and resilience were identified as protective factors against mental illness in FLWHA. Mental illness had a deleterious effect on viral suppression rates among FLWHA, resulting in delayed initiation of antiretroviral therapy treatment and increased mortality but had no impact on immune reconstitution in the face of ART adherence. Given the high prevalence rates of depression and anxiety and their relationship with HIV progression, it is crucial that mental health care services are integrated into routine HIV care.
Research Article
Keywords: Mental health burden; HIV; AIDS; sub-Saharan Africa